Decreased levels of ferritin, mild thrombocytosis, and increased erythropoietin are sequential events among frequent plateletpheresis donors: Implication for a ferritin screen. (December 2022) - Chin, Li-Te; Woon, Jun Yu; Kuo, Sau-Wei; Lu, Shih-Chien
Abstract: Background: It is generally recognized that repeat apheresis increases the risk for iron deficiency, thus may impact on the blood homeostasis. With regard to donor vigilance, we clarified the mid- to long-term effects of plateletapheresis by comparing the most frequent donors with the first-time ones in hematological and biochemical tests. Methods: Levels of erythropoietin (EPO), hemoglobin (Hb) and ferritin were analyzed in double-unit (500 mL whole blood or 6 × 10 11 apheresis platelets) donations in three male cohorts, with identifiers of first-time whole-blood donors ( n = 30), first-time platelet donors transited from maximal whole blood to apheresis ( n = 30) and frequent donors subjected to extreme plateletpheresis ( n = 90), respectively. According to the number of donations, the last earnest cohort, who donate almost 24 times a year, was further subdivided into three groups– casual (76–120 life-time donations in 5 years), mediocre (121–168 within 7 years) and enthusiastic (≥169 within 7 years and a month). Results: Regardless of the donation experience in whole blood or plateletpheresis, iron deficiency (serum ferritin concentrations <15 μg/L) was identified in all earnest cohorts. The ferritin means were significantly lower in plateletpheresis groups, with the lowest values in the enthusiastic group. EPO levels showed a significant inverse correlation with ferritin ( p = 0.015, r = –0.224). Long-term earnest donors had the lowest iron stores accompanied by a later thrombocytosis and a final increase in EPO was revealed. Conclusion: Regular ferritin screens are crucial to ensure a high level of donor health protection.